Oregano essential oil supplementation improves productive performance, oxidative stability, and lipid parameters in turkeys - Mendoza-Ordoñez, Gilmar (2020)
The present study evaluated the effect of supplementation with oregano essential oil (OEO) on the productive parameters, oxidative stability, and lipid parameters of turkey meat. Eighty 1-d-old male turkeys were randomly distributed into four treatments groups and fed the following diets for 105 d: control diet without any supplementation or supplementation with 300 mg/kg lincomycin and spectinomycin, 100 mg/kg OEO, or 200 mg/kg OEO. Supplementation with 200 mg/kg OEO obtained the best body weight, average daily gain, feed conversion, and the lowest feed intake with respect to the other diets (p < 0.001), while 100 mg/kg OEO had the best oxidative stability (p < 0.001). Though OEO had no hypocholesterolemic effect, 200 mg/kg OEO produced the lowest concentration of triglycerides in the blood (p < 0.05). In conclusion, OEO supplementation improves productive parameters and increases oxidative stability in turkeys. Therefore, OEO has the potential to act as a growth promoter replacing antibiotics.